2001
DOI: 10.1128/cmr.14.4.909-932.2001
|View full text |Cite
|
Sign up to set email alerts
|

Ross River Virus Transmission, Infection, and Disease: a Cross-Disciplinary Review

Abstract: SUMMARY Ross River virus (RRV) is a fascinating, important arbovirus that is endemic and enzootic in Australia and Papua New Guinea and was epidemic in the South Pacific in 1979 and 1980. Infection with RRV may cause disease in humans, typically presenting as peripheral polyarthralgia or arthritis, sometimes with fever and rash. RRV disease notifications in Australia average 5,000 per year. The first well-described outbreak occurred in 1928. During World War II there were more outbreaks, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
454
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 401 publications
(478 citation statements)
references
References 143 publications
(141 reference statements)
21
454
1
2
Order By: Relevance
“…Chikungunya virus (CHIKV), O'nyong-nyong virus, Mayaro virus, and Ross River virus are among a group of mosquito-transmitted alphaviruses that cause debilitating pain and inflammation of musculoskeletal tissue in humans. [1][2][3][4] These viruses are an emerging threat because of their ability to initiate explosive epidemics, 3,5 including a 1979 -1980 epidemic of Ross River fever in the South Pacific, which involved more than 60,000 patients, 3 and a 1959 -1962 epidemic of O'nyong-nyong fever in Africa, which involved at least 2 million patients. 6 In 2004, reemergence of CHIKV resulted in an epidemic that caused millions of cases in multiple countries in the Indian Ocean region, including 270,000 cases on Reunion Island and an estimated 1.4 million to 6.5 million cases in India.…”
mentioning
confidence: 99%
“…Chikungunya virus (CHIKV), O'nyong-nyong virus, Mayaro virus, and Ross River virus are among a group of mosquito-transmitted alphaviruses that cause debilitating pain and inflammation of musculoskeletal tissue in humans. [1][2][3][4] These viruses are an emerging threat because of their ability to initiate explosive epidemics, 3,5 including a 1979 -1980 epidemic of Ross River fever in the South Pacific, which involved more than 60,000 patients, 3 and a 1959 -1962 epidemic of O'nyong-nyong fever in Africa, which involved at least 2 million patients. 6 In 2004, reemergence of CHIKV resulted in an epidemic that caused millions of cases in multiple countries in the Indian Ocean region, including 270,000 cases on Reunion Island and an estimated 1.4 million to 6.5 million cases in India.…”
mentioning
confidence: 99%
“…RRV causes a non-fatal disease in humans, and it has been estimated that between 70 % and 90% of people infected with RRV have either mild symptoms or no symptoms at all [2]. The typical features of RRV infection are joint pain and swelling (mainly in the extremities), lethargy, myalgia, rash (involving the trunk and limbs), fever, headache and depression [3][4][5][6]. With thousands of cases occurring in Australia each year, the burden of this disease to Australian society is significant.…”
Section: Introductionmentioning
confidence: 99%
“…22 The transient nature of the viremia that develops in animals renders isolation of SAGV of little diagnostic value; consequently, antibody prevalence is frequently viewed as an indicator of infection. 3 The 51% seropositive rate (Table 3) found in this study indicated that about half of the pig population had been infected with SAGV before the survey. In particular, results of the SNA test for pigs from 2 offshore island districts, namely Penghu and Kinmen, indicated 100 and 79% seronegativity, respectively, and titer was lower than that in pigs on the main island, suggesting that, in these offshore districts, SAGV has not become widespread at this time.…”
Section: Discussionmentioning
confidence: 88%